EFEKTIVITAS PENERAPAN METODE JAS DALAM MENINGKATKAN HASIL BELAJAR KOGNITIF DAN MOTIVASI BELAJAR PESERTA DIDIK SMK MA’ARIF TEGALREJO PADA SUB MATERI KESEIMBANGAN LINGKUNGAN - Fadhil, Ahmad; P, Karunia G; Zikra, Zikra; Sukmawati, Ika (FKIP Universitas Tanjungpura, 2026)
This study aims to determine the effectiveness of the Natural Exploration Learning Method (JAS) in improving cognitive learning outcomes and learning motivation of students in the environmental pollution sub-material at SMK Ma'arif Tegalrejo. This study was motivated by low academic achievement and lack of student learning motivation, which were caused by the use of conventional learning methods thattend to be monotonous and less contextual. This study is a pre-experimental study with a one group pretest-posttest design, involving 28 class X TKR A students selected through purposive sampling techniques. The instruments used included multiplechoice tests to measure cognitive learning outcomes and psychological scales to measure learning motivation. Data analysis was carried out using the N-Gain test. The results showed that the application of the JAS method provided a significant increase in students' cognitive abilities, with an average N-Gain value of 0.6 which is included in the moderate category. The results of student learning motivation also increased, with an average N-Gain of 0.4 in the moderate category. The results of the study indicate that the JAS method is effective in improving students' learning outcomes and learning motivation on environmental balance material at SMK Ma'arif Tegalrejo.